Nutrition interventions integrated into an existing maternal, neonatal, and child health program reduce food insecurity among recently delivered and pregnant women in Bangladesh - Frongillo, Edward A.; Nguyen, Phuong Hong; Sanghvi, Tina; Mahmud, Zeba; Aktar, Bachera; Alayon, Silvia; Menon, Purnima (American Society for Nutrition, 2019)
Antenatal care may be a means to reduce food insecurity in pregnancy and postpartum periods. With the use of a cluster-randomized design, we tested whether participation in nutrition-focused antenatal care intending to improve household knowledge about the importance of nutrition for pregnant and lactating women and encourage allocation of household resources to ensure sufficient quality and quantity of foods, without providing food assistance, would reduce household food insecurity.